Star Island - Hiaasen, Carl (Alfred A. Knopf, 2010)
Ann DeLuisa, body double for drug-addled pop star Cherry Pye, is kidnapped by an obsessed paparazzo, and Cherry's entourage must rescue her while keeping her existence a secret from Cherry's public--and from Cherry herself.